PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN PADA MATA PELAJARAN IPA KELAS V SD CENTER MALAKAJI KAB.GOWA: PENELITIAN SKRIPSI - Insani Amalia; Arnidah; Abdul Hakim (STKIP Subang, 2023)
The development of digital technology today has a significant impact on the world of education. The use of technology facilitates the learning process and creates a learning atmosphere that is not monotonous. The objectives of this study were 1) to determine the level of need for learning video media, 2) to design learning video media, 3) to determine the validation of learning video media, 4) to determine the practicality of learning video media, 5) to determine the level of effectiveness of learning video media. This research was developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which was implemented at SD Center Malakaji Kab. Gowa. The research subjects consisted of 30 students, 1 teacher, and 2 validators who are experts in the field of material and media. Data were collected through needs assessment questionnaires, material validation, media validation, small group trials, large group trials, and teacher responses. The results of this study are: 1) the results obtained from the level of student needs show the qualification is quite needed. 2) in planning learning video media, Powtoon application is used. The results of this development are in the form of animated videos, which consist of four parts, namely introduction, presentation of material, practice questions, and conclusions. 3) validation from material experts and media experts showed very good results. 4) to test the feasibility level of the product, small group trials, large group trials and teacher responses were conducted. From the three trials, very good qualification results were obtained. 5) the results of the learning outcomes test (pre-test) showed a fairly good level of effectiveness, while the results of the learning outcomes test (post-test) showed a very good level of effectiveness. Based on the results of this study, it can be concluded that the products developed by researchers have a high level of validity, are practical in use, and effective in improving science learning.